FROM CHALKBOARDS TO CHATBOTS: AI TOOLS FOR PERSONALISED LEARNING IN HIGHER EDUCATION IN BANGLADESH - Haque, Md. Nazmul; Jahan, Mst. Musfak; Siddik, Abu Bokkor; Hossain, S M Saadat; Rahman, Mohammad Mustafizur (Universitas Negeri Makassar, 2026)
This study explores the potential of Artificial Intelligence (AI) tools to improve teaching-learning pedagogy at the universities in Bangladesh, focusing on the development of personalized learning pathways for educators and students. Applying a mixed-methods research design, data were collected from 10 teachers and 40 students of six universities through a Google Docs questionnaire. The findings indicate a widespread acknowledgement of AI tools for their capacity to generate ideas and to clarify complex concepts, provide instant feedback, and adapt educational experiences to meet individual requirements. Most of the respondents reported that AI tools helped them personalize their learning paths, manage study time more effectively, and improve overall understanding through customized resources. Faculty members also acknowledge the value of AI in supporting teaching practices, mentioning its role in preparing course plans and lectures, and enabling quick access to relevant information. However, participants raised important concerns about ethical challenges, such as plagiarism, over-reliance on technology, and possible negative impacts on critical thinking and creativity. They emphasize the need for proper guidance and institutional support to use AI responsibly. As AI offers significant benefits for higher education, the study suggests that adequate training, academic integrity, and a balanced approach to preserve meaningful human-machine interaction in the learning process are needed to integrate AI in education.